Model Perilaku Berwirausaha Perempuan Terdidik Minangkabau - Sari, Mareta Kemala; Megawati (Universitas Brawijaya, Indonesia, 2014)
This study is an explanatory research which aimed to identify the model of entrepreneurial behavior of educated Minangkabau's woman in West Sumatera through investigates the relationship between entrepreneurial attitude, Subjective Norm, self evocation as endogenous variable and entrepreneurial behavior as exogenous variable. Additionally, this study employs entrepreneurial intention as intervening variable. This study contributes to enhance the university graduate in their intention to be an entrepreneur. This study utilizes stratified random sampling technique by using questionnaire that sent to allpopulation namely the IWAPI member in West Sumatera. Prior to data analysis, the data were subjected to data preparation using SPSS 20. SPSS Version 20 was employed for data screening; demographic profiling of the respondents. In addition, Smart PLS will be employed to data analysis (measurement model and structural model).